PRAWO DO ZAWARCIA MAŁŻEŃSTWA. PERSPEKTYWA KANONISTY - Góralski, Wojciech (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The inherent human right to enter into marriage is at the same time the right of the faithful in Church, guaranteed in canon 1058 of the Code of the Canon Law. It constitutes a lasting basis for canonical marriage system. The right to marriage, however, is not absolute since it is subject to necessary restrictions. Apart from restrictions deriving from the law of God itself, there are restrictions which derive from the Church legislator; both result in the nullity of marriage. If it is to be decided when the law of God does not allow marriage, it is solely up to ultimate church authority (the Holy See). It also decides about ius connubii restrictions, but it can do so only for the greater good or to protect the value of marriage, and in some cases also for the welfare of the bride or groom themselves. The limitation of the right to enter into marriage deriving from the Church legislator is expressed above all in decisions about marriage obstacles and the canonical form of entering into marriage